Effect of Drinking Ration with Reduced Deuterium Content on Brain Tissue Prooxidant-Antioxidant Balance in Rats with Acute Hypoxia Model - Alexander A. Kravtsov; Stanislav V. Kozin; Ekaterina R. Vasilevskaya; Anna A. Elkina; Lilia V. Fedulova; Konstantin A. Popov; Vadim V. Malyshko; Arkady V. Moiseev; DenisI.Shashkov; Mikhail G. Baryshev (Journal of Pharmacy and Nutrition Sciences, 2018)
The aim was to investigate prooxidant-antioxidant system in the blood and brain homogenates functional activity in rats with acute hypoxia model with different deuterium/protium (D/H) ratios in drinking diet. Studies have shown that consuming DDW (–665 ‰) within 8 weeks lead to deuterium concentration decrease in blood plasma at 317 ‰ and brain at 209 ‰ of rats, in comparison to control group, consuming natural water. DDW consumption before hypoxia modeling in rats improves antioxidant defense enzymes (catalase, superoxide dismutase, glutathione peroxidase and glutathione reductase) activity in the blood, increasing its antioxidant potential by 20 %, while free radical oxidation intensity in plasma and biomolecules peroxide modification rate in erythrocytes. Also, in brain tissues consuming DDW, there were no abnormalities in catalase, superoxide dismutase activity, and it was noted increase (by 71 %) in reduced thiol-containing compounds concentration, which reduces nerve hypoxi? cell damage risk. Neuroprotective effect presence is confirmed by higher (by 32 %) antioxidant activity markers of lyophilized brain tissues, and by free radical oxidation lower intensity (by 13 %) and biomolecules oxidative modification rate (by 16 %) in these lyophilized tissues. Thus, the advisability of using DDW neuroprotective effects in cerebral circulation disturbance in experimental and clinical practice.